Limited palmar fasciectomy for bilateral Dupuytren’s contracture - Rao Venkata Mahipathy, Surya Rao; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Jayachandiran, Anand Prasath; Rajendran, Suresh (International Journal of Research in Medical Sciences, 2021)
Dupuytren’s disease is a fibro-proliferative condition affecting the palmar and digital fascia. This disease is very common in Northern Europe but in India it uncommon as there are only a few cases reported, hence also called as ‘Viking Disease’. Surgical fasciectomy is the standard surgical treatment of choice for Dupuytren’s disease. Complications following surgery are high but there is no definitive cure for Dupuytren disease (DD), and recurrence of finger contractures after treatment is common.